Validation and Method Development of Tadalafil in Bulk and Tablet Dosage Form by RP-HPLC - Bojanapu, A.; Subramaniam, A. T.; Munusamy, J.; Dhanapal, K.; Chennakesavalu, J.; Sellappan, M.; Jayaprakash, V. (Drug Research, 2015)
A novel, precise, rapid and sensitive reverse phase high performance liquid chromatographic method has been developed for the validated estimation of Tadalafil in bulk and tablet dosage form. The separation was achieved on Agilent Eclipse XDB C18 column (150 mm×4.6 mm, 5 µ) using a mobile phase that consists of the buffer (potassium dihydrogen orthophosphate) and acetonitrile in the ration of 50:50 V/V, pH 6 was adjusted with orthophosphoric acid. The flow rate was maintained at 1.2 ml/min and the detection wavelength was 285 nm. The method was validated for linearity, specificity, sensitivity as per ICH guidelines. The retention time was found to be 3.181 for Tadalafil. The calibration curve was linear over the concentration range of 10–150 µg/ml. The % RSD was satisfactory which showed the method found to be reliable. The high percentage recovery confirmed the suitability of the method for estimation of Tadalafil in pharmaceutical dosage form. The developed method could be applicable for routine analysis of Tadalafil in bulk and tablet dosage form.
Keywords: RP-HPLC; tadalafil; method development; validation